London in the Novels by Robert Galbraith: a text-world perspective - Kulchytska, Olga; Erlikhman, Anna (Respectus Philologicus, 2024)
The Strike series of contemporary crime fiction novels by Robert Galbraith exhibits an abundance of descriptions of real-life London. The aim of this article is to explore their functions in the context of the author’s works.Characteristic properties of the cityscapes in the novels are the merged perspectives of the omniscient narrator and a character, foregrounded details, contrasts in images and attitudes, and the use of metaphor and personification. Text World Theory allows us to explain how they aid in constructing mental representations, or text-worlds, of the city and examine functions fulfilled by the depictions of London in R. Galbraith’s fiction: (1) emphasising connectedness between the discourse- and text-worlds, (2) creating an atmospheric background, (3) broadening readers’ understanding of characters, (4) making London a character in its own right, (5) advancing the story. The first function is typical of all the text-worlds analysed; it indicates the real-world nature of fictional information as a distinctive feature of the Strike series.